GENDER JUSTICE IN INDIA:THE CONSTITUTIONAL PROMISE AND THE LIVED REALITY - Sinha, Shubha; Pandey, Srikant (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Despite constitutional promises of equality and social justice, Indian women continue to face deep-rooted discrimination, marginalization, and violence. The struggle for gender equality in India is marked by a persistent gap between the ideals enshrined in the Constitution and the lived realities of women. Social structures grounded in patriarchy, economic exclusion, and cultural traditions continue to deny women equal status and access to justice.